A high-efficiency red light-emitting module utilizing PLCC packaging for plant lighting applications - Hu, Limin; Hu, Yingying; Xia, Yu; Peng, Haiping; Wei, Shaokun; Shi, Yan (Frontiers in Physics, 2025)
With the increasing adoption of LEDs in plant lighting applications, reducing costs and enhancing light efficiency have emerged as key research priorities in this domain. Currently, light-emitting modules in LED plant lighting systems predominantly employ ceramic packaging, with PLCC packaging being seldom utilized due to its lower light extraction efficiency. This study introduces a novel approach by incorporating both planar optical encapsulant and the filler material in the assembly of red light chips, achieving a 22% improvement in light efficiency. By addressing this technical limitation, the design effectively reduces costs, resulting in a cost-effective light-emitting module with high light extraction performance. Furthermore, the design was tested with multiple chips, demonstrating significant potential for further optimization and advanced design applications.